Investigation of the mechanical performance of the composite prosthetic keel based on the static load: a computational analysis - Subhi, Kussay Ahmed; Hussein, Emad Kamil; Al-Hamadani, Haider Rahman Dawood; Sharaf, Hussein Kadhim (Eastern-European Journal of Enterprise Technologies, 2022)
In this paper, the numerical simulation of the mechanical performance of a composite prosthetic keel structure under static load has been explored, and the findings of this inquiry have been included. The prosthetic keel is constructed from an epoxy and glass fiber composite, 3 percent weight (MWCNTs with SiC), and a carbon nanotube, which are utilized in conjunction with other materials to create the structure. The force that is applied in this example is 1,000 N, and it is applied in accordance with the boundary condition that has been previously established in this case. The ANSYS modeling software package was used to create the prosthetic keel model, which was meshed and created. Because of the total deformation, the fundamental simulation results of the prosthetic keel model have been converged in line with the total deformation, which was used as a reference to determine the total deformation. The major outcome of the current numerical analysis has been successfully validated by considering the findings of the earlier experimental study. The mechanical performance of the composite prosthetic keel structure is determined by four primary criteria, the results of which are based on the findings. Aspects to analyze include equivalent elastic strain, three-axis directed deformation, total deformation, and equivalent stress (von Mises). Although only 0.00058 mm total deformation is created by the imposed static load of 1,000 N (the least attainable value), it represents the largest total deformation. The equivalent stress (von Mises) responded to the load with a response of 0.045 MPa, which is quite small. Furthermore, the equivalent elastic strain has also been undertaken and it resulted in a value of elastic strain of 3.4*10^7.